Enhancing the electrochemical performances of Li2S-based cathode through conductive interface design and addition of mixed conductive materials. (10th November 2021) - Liu, Hong; Zeng, Peng; Yu, Hao; Zhou, Xi; Li, Zhi; Chen, Manfang; Miao, Changqing; Chen, Gairong; Wu, Tianjing; Wang, Xianyou
Highlights: Polypyrrole coating is utilized for polysulfides immobilization. Lithium sulfide is wrapped inside cathode from exposure. Activation barrier and polysulfides shuttle are greatly suppressed. Electrochemical performances of as-prepared cells are promoted. Abstract: The significantly-high theoretical energy density and eco-sustainability of lithium sulfur batteries (LSBs) arouses a rapid surge of interest in recent years. However, some key issues of cathode, for instance, the polysulfides confinement, low ion/electrons transfer and etc., hinder the practical utilization of LSBs. Herein, such issues could be carefully handled by using the conductive polypyrrole as polysulfides wrapper. The polypyrrole with pyrrole rings can efficiently confine polysulfides inside cathode for redox. Meanwhile, the conductive polypyrrole with delocalized π-electron cloud can facilitate electrons transfer. Besides, the addition of carbon nanotube (CNT) and oxidized graphene (GO) can enhance the conductivity of cathode material. As a result, the Li2 S/CNT/GO/PPy cathode delivers a cycling capacity of 525 mAh g −1 with a low-capacity decay rate of 0.065 % cycle −1 after 400 cycles. Therefore, the lithium-sulfur battery with Li2 S-based and PPy-wrapped cathode could reasonably be counted as a potential alternative of long-cycling Li-ion cells. Graphical abstract: Image, graphical abstract